An Overview of the Evidence and Mechanism of Drug–Herb Interactions Between Propolis and Pharmaceutical Drugs - Hossain, Sanowar; Yousaf, Muhammad; Liu, Yang; Chang, Dennis; Zhou, Xian (Frontiers in Pharmacology, 2022)
With the growing interest in medicinal use of propolis, numerous studies have reported significant interactions between propolis extract and pharmaceutical drugs which may result in great clinical benefits or risks. The present study aims to review the drug-herb interactions of the full-spectrum propolis extract and main pharmaceutical drugs from both pharmacodynamic and pharmacokinetic aspects, and elucidate the underlying pharmacological mechanisms. A literature search was conducted between June 2021 and February 2022 in Google Scholar, PubMed, MEDLINE, EMBASE databases to include English studies from year 2000 to 2022 that evaluated the interaction of full-spectrum propolis extract and standard pharmaceutical drugs/cytochromesP450s. Studies that looked into geopropolis, propolis fractions and isolated compounds, or interaction of propolis with foods, bioactive molecules or receptors other than standard pharmaceutical drugs were excluded. From pharmacodynamic perspective, propolis extract exhibited positive or synergistic interaction with several chemotherapeutic drugs by enhancing anti-tumor activity, sensitizing the chemo-resistance cell lines and attenuating multi-organ toxicity. The molecular mechanisms were associated with upregulating the apoptotic signal, immunomodulatory activity, and attenuating oxidative damage. Propolis extract also enhanced the anti-bacterial and anti-fungal activities of many antimicrobial drugs against sensitive and resistant organisms, with stronger effect against the gram-positive bacteria than that of the gram-negative bacteria. The synergistic action was related to strengthened action on interfering cell wall integrity and protein synthesis. The strong antioxidant activity of propolis also strengthened the therapeutic effect of metformin in attenuating hyperglycemia and pancreatic damage as well as mitigating oxidative stress in liver, kidney, and testis. In addition, propolis showed potential capacity to enhance short-term and long-term memory function together with donepezil, improve motor function with levodopa, and parasite killing activity with praziquantel. Pharmacokinetic studies showed inhibitory activities of propolis extracts on several CYP450 enzymes in vitro and in vivo, however, the effects on those CYP450 were deemed insignificant in human which may be attributed to the low bioavailability of the contributing bioactive compounds when administered in the body. The enhanced bioactivities of propolis and main pharmaceutical drugs support the use of propolis in integrative medicine in anti-cancer, anti-microbial, antidiabetic, neurological disorders, with low risk of altered pharmacokinetic activities.